Analysis of corrugated web beam to column extended end plate connection using LUSAS software - Alisibramulisi, Anizahyati (2006)
Bolted extended end plate connections are commonly used in rigid steel frame. Inappropriate or inadequate connections of beam and column are hazardous and can lead to collapses and fatalities. Although laboratory testing is more accurate in analyzing the connection, but unfortunately it is time consuming and quite expensive. Thus, this project is intended to develop a Finite Element Analysis (FEA) approach as an alternative method in studying the behavior of such connections. The software being used is LUSAS 13.5 and the model used was an extended end plate, welded to the end of a corrugated web beam and then bolted to the column-flange. This type of connection will cause the column to bend about its major axis, and affect the end plate, bolts and corrugated web beam. Therefore, the analysis will be much more difficult as compared to plain web beam. The moment-rotation (M-f) response of the joint was plotted in term of a M-f curve, and then, it was superimposed with the curve taken from an existing experimental result. It was found that the two curves shared the same stiffness at the elastic stage of the loading and they started to diverge as the connection became plastic. However, the LUSAS moment of resistance is 50% more than that obtained in the experiment. Further investigations are necessary to improve the finite element prediction.